Determinants of Internal Audit Quality and External Audit Fees - Wilamsari, Feni; Musriati, Titik; Cahyaningati, Retno (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2024)
Internal audit a part of good corporate governance, one of its functions is to ensure that internal control runs well, apart from that, the existence of internal audit also expected to provide value added to the company. Quality internal audit plays a very important role in supporting the success and sustainability of a company. This research aims to examine the determinants of internal audit quality and further examine the role of internal audit quality on external audit fees. Primary data is used in this research, the collection method is through distributing questionnaires. Purposive sampling criteria were used in this research as a sample selection technique.and obtained a total of 43 samples. Data Analysis Method using Confirmatory Factor Analysis with PLS3. The object is the internal audit of companies that are members of the Japfa Group. The research results show that competence and objectivity are determinants of internal audit quality. Furthermore, internal audit quality has  significant effect on external audit fees.